Assessing the real-world safety of tralokinumab for atopic dermatitis: insights from a comprehensive analysis of FAERS data - Zhao, Kaidi; Zhao, Yang; Xiao, Shengxiang; Tu, Chen (Frontiers in Pharmacology, 2024)
Background: Tralokinumab, a humanized monoclonal antibody targeting interleukin-13, has been primarily used for the treatment of moderate-to-severe atopic dermatitis. Given its extensive use in clinical practice, understanding its safety profile in the real-world setting is crucial.This study utilized disproportionality analysis to evaluate the safety of tralokinumab in clinical practice by analyzing all adverse event reports since 2021 in the FDA Adverse Event Reporting System database that identified tralokinumab as the primary suspected drug. Reporting odds ratio, proportional reporting ratio, multi-item gamma Poisson shrinker, and Bayesian confidence propagation neural network were used for disproportionality analyses of adverse events related to tralokinumab.Additionally, the Weibull distribution was employed to model the risk of adverse events over time.Results: Adverse reactions documented on the drug label, such as injection site reactions, conjunctivitis, and upper respiratory infections, displayed positive signals.Additionally, potential adverse reactions not mentioned on the label were also identified, including dizziness, headache, nausea, vomiting, hair loss, and acne. The importance of adverse event monitoring, particularly in the first month after treatment initiation, was emphasized.This study has provided preliminary safety data on the real-world 3 application of tralokinumab, confirming some known adverse reactions and revealing additional potential risks. The findings offer critical safety information for clinicians prescribing tralokinumab to treat atopic dermatitis.